Seleksi Tertulis Bakal Calon Kepala Desa yang Memenuhi Persyaratan Administrasi di Kabupaten Buton Tahun 2021 - Cecep Nuryadin; Hardin Hardin; Indah Kusuma Dewi; Herman Lawelai; Darojatun Andara (Edumedia Solution, 2022)
This community service aims to carry out an analysis and describe the implementation of a written selection of Village Head Candidates Who Meet Administrative Requirements in Buton Regency in 2021. The implementation of community service has been carried out in accordance with the provisions where the selection process is carried out offline. The test is carried out in the form of multiple-choice questions and essays with a total of 40 and 5 questions, respectively. The selection results showed that the participants with the highest score of 5 in each village had the right to be appointed as village head candidates. In addition, community service has been carried out professionally and responsibly in the form of selecting village head candidates. Reliable selection and accountability will result in quality village governance. The existence of a competent village head will result in village progress